Pyridine-based complexes of copper(II) chloride and bromide: ligand conformation effects on crystal structure. Synthesis, structure and magnetic behavior of Cu(2-Cl-3-X′py)2X2 [X, X′ = Cl, Br]. Issue 11 (3rd June 2019) - Dubois, Robert J.; Landee, Christopher P.; Rademeyer, Melanie; Turnbull, Mark M.
Abstract: Reaction of copper(II) chloride or bromide with 2-chloro-3-bromopyridine or 2, 3-dichloropyridine generates a family of compounds of the general formula L2 CuX2 (1 –4 ). X-ray crystallography shows that the bromide complexes (3-bromo-2-chloropyridine)dibromidocopper(II) (1 ) and (2, 3-dichloropyridine)dibromidocopper(II) (3 ) are particularly unusual in that they crystallize with both the syn- and anti-conformation structures in the same crystal. A review of the literature on complexes of the formula (substituted-pyridine)2 CuX2 suggests that these are the first examples of such complexes. The members of the family show a variety of magnetic behaviors and variable temperature magnetic susceptibility data indicate that1 is essentially paramagnetic (θ = −0.9(1) K) while3 is weakly ferromagnetic ( J  = 2.9(1) K). Compound2 [(3-bromo-2-chloropyridine)dichloridocopper(II)] is fit by the uniform 1-D antiferromagnetic model ( J = −19.6(1) K), while4 [(2, 3-dichloropyridine)dichloridocopper(II)] exhibits weak anti-ferromagnetic interactions ( J = −3.68(3) K). Abstract :